Effect of Baccharis dracunculifolia DC (Asteraeeae) extracts and its isolated compounds on macrophage activation - Missima, Fabiane; da Silva Filho, Ademar A.; Nunes, Gladston A.; Pires Bueno, Paula C.; de Sousa, Joao Paulo B.; Bastos, Jairo K.; Sforcin, Jose M. (Pharmaceutical Press-royal Pharmaceutical Soc Great Britian, 2007)
Baccharis dracunculifolia D.C. (Asteraceae), a shrub which grows wild in Brazil, is the main botanical source of Brazilian green propolis. Since Brazilian propolis shows an immunomodulatory activity, the goal of this work was to evaluate the action of B. dracunculifolia extracts and some of its isolated compounds on reactive oxygen intermediate (H2O2) production by macrophages obtained from male BALB/c mice. The results showed that the leaf (Bd-L) (25, 50, and 100 mu g mL(-1)), leaf rinse (Bd-LR) (25 mu g mL(-1)), and the root (Bd-R) (25 mu g mL(-1)) extracts enhanced H2O2 release by macrophages. A phytochemical study of the root and leaves of B. dracunculifolia was carried out. The chromatographic fractionation of Bd-R, using several techniques, afforded the isolation of baccharis oxide (1), friedelanol (2), viscidone (11), 11-hydroxy-10,11-dihydro-euparin (12), and 6-hydroxy-tremetona (13), while Bd-LR gave the following isolated compounds: baccharis oxide (1), friedelanol (2), isosakuranetin (3), aromadendrin-4'-methyl ether (4), dihydrocumaric acid (5), baccharin (6), hautriwaic acid lactone (7), hautriwaic acid acetate (8), drupanin (9), and cumaric acid (10). Among the isolated compounds, baccharis oxide (1) and friedelanol (2) increased H2O2 production at a concentration of 1001,M. This is the first time that the presence of compounds 7, 8, 12, and 13 in B. dracunculifolia has been reported. Based on these results it is suggested that the crude extracts and some isolated compounds from B. dracunculifolia display an immunomodulatory action.